(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1913)
The axe, which was found in the vicinity of an earlier discovery of a bronze sword, is a well-preserved example of the socketed and looped variety. The objects are broadly contemporary and could have been deposited together. The stone mould was an isolated find. A very fine button mould with an inscription dated 1659 is described in detail.